Health-related quality of life after prophylactic cranial irradiation for stage III non-small cell lung cancer patients: Results from the NVALT-11/DLCRG-02 phase III study. (March 2020) - Witlox, W.J.A.; Ramaekers, B.L.T.; Joore, M.A.; Dingemans, A.-M.C.; Praag, J.; Belderbos, J.; Tissing-Tan, C.; Herder, G.; Haitjema, T.; Ubbels, J.F.; Lagerwaard, J.; El Sharouni, S.Y.; et al.
Highlights: Scores of the HRQoL metrics were not different between PCI and observation. HRQoL was lower in patients with neurocognitive symptoms and BM. The utility score was lower in patients with neurocognitive symptoms without BM. Also, the EQ VAS was lower in patients with neurocognitive symptoms without BM. Abstract: Background and purpose: The NVALT-11/DLCRG-02 phase III trial (clinicaltrials.gov identifier: NCT01282437) showed that, after standard curative intent treatment, prophylactic cranial irradiation (PCI) decreased the incidence of symptomatic brain metastases (BM) in stage III non-small cell lung cancer (NSCLC) patients compared to observation. In this study we assessed the impact of PCI on health-related quality of life (HRQoL). In addition, an exploratory analysis was performed to assess the impact of neurocognitive symptoms and symptomatic BM on HRQoL. Materials and methods: Stage III NSCLC patients were randomized between PCI and observation. HRQoL was measured using the EuroQol 5D (EQ-5D-3L), EORTC QLQ-C30 and QLQ-BN20 instruments at completion of standard curative intent treatment and 4 weeks, 3, 6, 12, 24 and 36 months thereafter. Generalized linear mixed effects (GLM) models were used to assess the impact of PCI compared to observation over time on three HRQoL metrics: the EORTC QLQ-C30 global health status and the EQ-5D-3L utility and visual analogue scale (EQ VAS) scores. Results: In total, 86 and 88 patients were included in the PCI and observation arm, with a median follow-up of 48.5 months (95% CI 39–54 months). Baseline mean HRQoL scores were comparable between the PCI and observation arm for the three HRQoL metrics. In the GLM models, none of the HRQoL metrics were clinically relevant or statistically significantly different between the PCI and the observation arm ( p -values ranged between 0.641 and 0.914). Conclusion: No statistically significant nor a clinically relevant impact of PCI on HRQoL was observed.